Genomic and phenotypic characterization of Vibrio cholerae non-O1 isolates from a US Gulf Coast cholera outbreak. - Bradd J Haley; Seon Young Choi; Christopher J Grim; Tiffiani J Onifade; Hediye N Cinar; Ben D Tall; Elisa Taviani; Nur A Hasan; Abdulshakur H Abdullah; Laurenda Carter; Surasri N Sahu; Mahendra H Kothary; et al. (PLoS ONE)
Between November 2010, and May 2011, eleven cases of cholera, unrelated to a concurrent outbreak on the island of Hispaniola, were recorded, and the causative agent, Vibrio cholerae serogroup O75, was traced to oysters harvested from Apalachicola Bay, Florida. From the 11 diagnosed cases, eight isolates of V. cholerae were isolated and their genomes were sequenced. Genomic analysis demonstrated the presence of a suite of mobile elements previously shown to be involved in the disease process of cholera (ctxAB, VPI-1 and -2, and a VSP-II like variant) and a phylogenomic analysis showed the isolates to be sister taxa to toxigenic V. cholerae V51 serogroup O141, a clinical strain isolated 23 years earlier. Toxigenic V. cholerae O75 has been repeatedly isolated from clinical cases in the southeastern United States and toxigenic V. cholerae O141 isolates have been isolated globally from clinical cases over several decades. Comparative genomics, phenotypic analyses, and a Caenorhabditis elegans model of infection for the isolates were conducted. This analysis coupled with isolation data of V. cholerae O75 and O141 suggests these strains may represent an underappreciated clade of cholera-causing strains responsible for significant disease burden globally.